2011
DOI: 10.1161/circoutcomes.111.960971
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit With Drug-Eluting Stents in Observational Studies

Abstract: 2004 -2006 versus 2007) as the instrument, demonstrated no significant difference in 1-year mortality (predicted absolute difference, 2.0%; 95% CI, -1.8% to 5.7%; Pϭ0.30) and a strong trend toward reduced TLR with DES use (predicted absolute difference, -4.2%; 95% CI, -8.8% to 0.4%; Pϭ0.07). Conclusions-Among unselected PCI patients in contemporary practice, DES use tended to be associated with a consistent reduction in TLR regardless of risk-adjustment method but showed discordant effects on mortality with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…To address this, we used 1:6 matching to use the larger patient pool. 18,19 Propensity score matching was performed using nearest-neighbor matching and matching without replacement. 17 Cumulative mortality rates were also presented as Kaplan-Meier curves and compared with a stratified log-rank test.…”
Section: Propensity Score Matchingmentioning
confidence: 99%
“…To address this, we used 1:6 matching to use the larger patient pool. 18,19 Propensity score matching was performed using nearest-neighbor matching and matching without replacement. 17 Cumulative mortality rates were also presented as Kaplan-Meier curves and compared with a stratified log-rank test.…”
Section: Propensity Score Matchingmentioning
confidence: 99%
“…However, such differences in covariates between IV-stratified groups are often reported in IV analyses. 14,15 We also calculated the covariate imbalance using the Mahalanobis distance, which corrects for observed covariance among measured covariates. Stratification by the IV resulted in an 87% reduction in Mahalanobis distance, indicating a significant improvement in covariate balance.…”
Section: Instrumental Variable Analysismentioning
confidence: 99%
“…Second, it is unknown to what extent population differences in socioeconomic status, postprocedural medication use, and other variables not measured in this study were present. As discussed, incomplete adjustment for baseline risk factors and unmeasured variables is a limitation inherent to observational studies and has been recently examined in PCI registry analysis by Venkitachalam et al, 27 who compared patients who received DES and BMS in a large registry and found that the use of different adjustment methods demonstrated different relative outcomes with DES and BMS. The difference in outcomes was potentially due to the presence of unmeasured confounders.…”
Section: Limitationsmentioning
confidence: 99%
“…This analysis strengthens the validity of our findings, but further study is still needed to understand causative factors for the significant mortality benefit with DES seen in our study, as well as other observational studies comparing DES and BMS. 8,27 Third, the classification of patients into racial and ethnic groups was based on hospital report and may differ significantly from self-report. Furthermore, broad racial and ethnic categories represent several subpopulations with potentially widely different cardiovascular risk profiles.…”
Section: Limitationsmentioning
confidence: 99%